Pelatihan Penyusunan Laporan Keuangan Sederhana Untuk Sekolah Di SMKS Tangerang Selatan - Danang Choirul Umam; Lukmanul Hakim; Ghea Astrid Sunanto (Jurnal Pengabdian Kepada Masyarakat Kalam, 2026)
Financial management plays a crucial role in ensuring transparency, accountability, and sustainability in educational institutions, including vocational and music schools. However, many schools still face challenges in preparing systematic and accurate financial reports due to limited accounting knowledge and inadequate administrative skills. This community service program aimed to enhance the capacity of administrative staff and treasurers of music schools/SMKS in Tangerang Selatan in preparing simple financial statements. The program was implemented through an educational and participatory approach, combining theoretical explanations with hands-on practice using simple financial recording formats. The results indicate that participants showed improved understanding of basic accounting principles, transaction recording, and the preparation of simple financial reports. In addition, the program increased participants’ awareness of the importance of transparent and accountable financial management as part of good school governance. Overall, this community service activity contributed positively to strengthening financial administration practices in schools and is expected to support sustainable and professional educational management.